The Consistency of Sex Ratio of Drosophila melanogaster (Meigen) in Different Physical Environment Condition - Fauzi, Ahmad; Ramadani, Shefa Dwijayanti; Sukmawati, Ika (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green TechnologyDO - 10.18860/icgt.v8i1.535, 2017)
Several environmental factors have been reported affect sex ratio in many organisms. The environmental factors that affecting sex ratio could from physical, chemical, or biological factors. In this study, the effect of some physical factors on sex ratio in D. melanogaster were studied. In normal laboratory condition, high temperature, dark condition, and EMF exposure, the sex ratio were 0.91:1.09, 1.00:1.00, 0.89:1.11, and 1.01:0.99 respectively. From the result, it can be seen that males and females adult filial number ratios in each group were close to 1:1.